A multi-stage mesoscopic numerical approach to simulate the flexural behavior of concrete beams with corroded rebars. (15th October 2021) - Jin, Liu; Yang, Hongshen; Zhang, Renbo; Du, Xiuli
Highlights: A multi-stage mesoscopic model involving rebar corrosion is established. The cracking pattern and the expansion pressure on concrete cover due to corrosion is analyzed. The flexural performances of RC beams are affected by corrosion level and corrosion mode. The bearing capacity of the beams in service is predicted based on simulation data. Abstract: Corrosion is the main factor affecting the service performance of reinforced concrete (RC) structures, especially in offshore or coastal areas. In this paper, taking RC beam as the research object, a three-dimensional meso-scale numerical model involving rebar corrosion was established. The corrosion effects on the mechanical behavior of RC beam was explored through a multi-stage analysis method (namely, corrosion induced expansion stage and structural deterioration stage). The non-uniform radial displacement was applied to concrete around the steel to simulate the expansion of rebar corrosion. The cracking process and the damage pattern of concrete caused by corrosion can be obtained. Then, taking this state as the initial condition, the mechanical analysis of corroded RC beam was carried out. The agreement between the numerical and the test results validates the rationality and correctness of the multi-stage analysis model. According to the simulation results, the concrete damage due to corrosion is mainly concentrated in the diagonal of reinforcement and the middle of adjacent reinforcement. The rust expansion pressure increases gradually when the corrosion level increased. For severely corroded beams, the concrete strain no longer conforms to the plane section assumption. In addition, corrosion reduces the bearing capacity and ductility of the beams. The coupling effects of corrosion of tensile and compression bars on the performance of the beam are more serious than that of only corrosion of tensile bars. Based on the data regression, a relationship to evaluate the bearing capacity of beams was established. It indicates that the flexural bearing capacity decreases by about 1.4%, 1.7% annually in the conditions of tensile reinforcement corroded only and both tensile and compressive reinforcement corroded.